Educating for Citizenship and Social Justice Practices for Community Engagement at Research Universities (Springer International Publishing, 2018)
In this edited volume, authors explore the ways in which departments, programs, and centers at public research universities are working to better engage students in the work of citizenship and social justice. The chapters in this book illuminate the possibilities and challenges for developing community engagement experiences and provide evidence of the effects of these efforts on undergraduates' development of citizenship outcomes and on communities. This text reveals how important the integration of our intentions and actions are to create a community engaged practice aimed towards justice. .